2015
DOI: 10.1016/j.algal.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and Na2CO3 catalyst on hydrothermal liquefaction of algae

Abstract: Hydrothermal liquefaction (HTL) has been identified as an innovative technique to convert aquatic or wet biomass such as algae into biofuels. In this study, HTL was performed on three algae strains viz. Nannochloropsis, Pavlova and Isochrysis at three temperatures of 250, 300 and 350 o C, with and without using Na 2 CO 3 as catalyst and a holding time of 60 minutes. The effect of temperature on the HTL product yields and their properties were studied for both catalytic and non-catalytic HTL. Maximum bio-oil yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(70 citation statements)
references
References 47 publications
8
61
1
Order By: Relevance
“…The observation is in agreement with the ESI-MS results that the HTL bio-oil from BSU-3 has slight lower molecular weight, which is favorable to gasoline and other light chemicals [18,32]. The boiling temperature range from 200 to 4008C was contributed to the long carbon chain (C [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ) compounds.…”
Section: Boiling Point Of Bio-oilsupporting
confidence: 90%
See 2 more Smart Citations
“…The observation is in agreement with the ESI-MS results that the HTL bio-oil from BSU-3 has slight lower molecular weight, which is favorable to gasoline and other light chemicals [18,32]. The boiling temperature range from 200 to 4008C was contributed to the long carbon chain (C [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ) compounds.…”
Section: Boiling Point Of Bio-oilsupporting
confidence: 90%
“…This could be due to the presence of air in the reaction vessel headspace [24]. Similar results were also observed by Shakya et al [25] when producing bio-oil via HTL of algae (Nannochloropsis, Pavlova, and Isochrysis) using Na 2 CO 3 as catalyst.…”
Section: Htl Bio-oil Gas and Residual Solid Yieldssupporting
confidence: 81%
See 1 more Smart Citation
“…They reported that the char yield decreased from 250 to 300°C; however, no significant effect was observed on increasing the temperature to 350°C. 22 In their following study, 23 they conducted HTL of Chlorella, Nannochloropsis, Pavlova, and Scenedesmus at 280 and 320°C and reported similar trends for yields of bio-oil, water-soluble fractions, and char with the reaction temperature. They also reported that, in most of the algal species, NH 4 + yields increased with the increase of reaction temperature from 280 to 320°C.…”
Section: Resultsmentioning
confidence: 84%
“…Shakya et al 22,23 measured yields of products (bio-oil, char, water-soluble products, and gas), total acid number of the products, pH, density, heating value, ash, moisture, and elemental composition of bio-oils produced after HTL of different strains of microalgae at various temperatures in the absence and presence of Na 2 CO 3 . They concluded that other than the product yield, the use of Na 2 CO 3 had no significant effect on the properties of the bio-oil, 22 and the obtained APs contained a large amount of total organic carbon (12−43 g/L), chemical oxygen demand (35−160 g/L), total nitrogen (1−18 g/L), ammonium (0.34−12 g/L), and phosphate (0.7−12 g/ L). 23 It has been reported that the reaction mechanism of HTL of algae involves four consecutive steps: (1) hydrolytic depolymerization of the proteins and carbohydrates to form water-soluble monomers such as peptide fragments, amino acids, and carbohydrate derivatives; (2) degradation of the monomers by dehydration, deamination, and decarboxylation;…”
Section: Introductionmentioning
confidence: 99%